Production and identification of peptides with activity promoting osteoblast proliferation from meat dregs of Pinctada martensii. Issue 9 (10th August 2021) - Tian, Yufeng; Jiang, Pingyingzi; Liu, Xiaoyue; Wei, Lulu; Bai, Yunxia; Liu, Xiaoling; Li, Shubo
Abstract: As a by‐product of pearl production, Pinctada martensii meat dregs have a high level of protein but cannot be fully utilized. In this study, P . martensii meat dregs were first hydrolyzed by three pepsin enzymes, resulting in neutral proteinase enzymatic hydrolysate that had a higher effect on stimulating the proliferation of MC3T3‐E1 cells, and cell proliferation increases of 37.37 ± 0.03%. Subsequently, after purification of alcohol precipitation, ultrafiltration, and Superdex G‐25 gel chromatography, five fractions were further separated and purified in which fraction ZP2 could effectively improve cell proliferation induced an increase of 43.95 ± 0.03% in MC3T3‐E1 cells growth. Consequently, with the help of alkaline phosphatase and methyl thiazolyl tetrazolium assay, five novel peptides (FDNEGKGKLPEEY, FWDGRDGEVDGFK, VLQTDNDALGKAK, IVLDSGDGVTH, and MVAPEEHP) derived from fraction ZP2 with the strongest osteogenic activity were screened, and their sequences were identified using Orbitrap Fusion Lumos Tribrid Orbital liquid chromatography‐mass spectrometry. Therefore, the research results demonstrated that P. martensii meat could be used as a promising material for producing food additives for improving osteoporosis. Practical applications: In this study, after enzymolysis and purification, the fraction ZP2, derived from Pinctada martensii meat dregs were found to have a better activity of promoting osteoblast proliferation, showing the higher osteogenic activity with an increase of 43.95 ± 0.03% in terms of cell proliferation. It is beneficial to realize the high value and resource utilization of P. martensii meat dregs as a by‐product of pearl production. The research demonstrated that the meat dregs of P. martensii could be used as an attractive material for producing active peptides in functional foods. In addition, the molecular weight of the peptides we identified from the ZP2 fraction is suitable for the proliferation of MC3T3‐E1 cells, which lays a foundation for the further synthesis of peptides that promote the high proliferation activity of osteocytes. Abstract : As a by‐product of pearl production, Pinctada martensii meat dregs was used to isolate and purify peptides with osteogenic activity after the subsequent extraction of bio‐zinc and taurine from P. martensii meat. After enzymolysis and purification, the fraction ZP2 derived from P. martensii meat dregs were found to have a better activity of promoting osteoblast proliferation. Five novel peptides derived from the fraction ZP2 with the strongest osteogenic activity were characterized by liquid chromatography–mass spectrometry.